Evaluación de la viabilidad y calidad de la semilla de quinua (Chenopodium quinoa), tras diferentes métodos de secado - Suntasig Caillagua, Maritza Elizabeth (2017)
The main objective of this study was to assess the feasibility of applying microwave drying on conservation of agricultural seeds. In order to that, the viability of quinoa seeds was evaluated in comparison with traditional drying methods (environmental drying and conventional oven). Conventional oven drying was performed at 55 ºC and microwave drying was carried out at three different power densities. The seed drying curve was determined for each treatment; the drying curve relate humidity lost with drying time. Thus, it was possible to know the recommended time needed for each drying technology to reach the optimum humidity for seed conservation establishes as 6-8%. It was proved that microwave drying reduces the drying time and energetic consumption. After conventional and microwave seed drying, it was valuated the germination rate in comparison with environmental seed drying by germination tests in Petri dishes of all treatments. It was found differences in the germination rate between treatments, showing lower germination those seeds microwave dried. Also, the field viability of the treatments with better germination rate was evaluated. It was tested that plants from microwave dried seeds presented a lower germination rate and field viability. Moreover, those plants had a lower height at the beginning of the cultivation. The results of this research show that microwave technology reduces the drying time of quinoa seeds and energy consumption, however it has an adverse effect in the seed quality, affecting severely the germination rate.